ANALYSIS OF MORPHOLOGICAL LANGUAGE ERRORS IN NEWS WRITING MEDIA CENTER ROKAN HILIR - Haryani Pitri; Hermaliza (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
A language error is a language that occurs when the use of language does not conform to standard grammar found in online or print media, both orally and in writing. In addition to print media, language errors also frequently occur in online media, one of which is the Rokan Hilir Media Center. The Rokan Hilir Media Center is an online-based information website or an information center for the public regarding disaster developments and community life in Rokan Hilir. As a government mass media, the use of language in every news item certainly has educational value and serves as an example for the public. However, in practice, various forms of language inaccuracies are often found, especially at the morphological level. This condition makes the Rokan Hilir Media Center a relevant object to be studied in language error analysis research. This study aims to describe the forms of language errors at the morphological level in news writing on the mediacenter.rohilkab.id page. The phenomenon of morphological errors in mass media, especially local government online media, is important to study because the media plays a role as a language educator for the community. This study uses a qualitative approach with a content analysis method. The data source in this study is news in the Rokan Hilir Media Center, while the data in this study are sentences that contain morphological errors. Data collection was carried out through documentation techniques and hermeneutic techniques (read-note-conclude). Data analysis includes the stages of data reduction, data presentation, and drawing conclusions. The results of the study indicate that there are various forms of morphological errors in the writing of Media Center news, including: morph replacement, inappropriate use of affixes, word formation with the confix di-…-kan, omission of affixes, sounds that should be luluh but are not diluluh, incorrect determination of basic forms, inappropriate use of words, and inappropriate repetition of compound words. Of the 103 error data found, the types of errors encountered with the number of errors were morph substitution (34), word formation with the confix di-…-kan (20), inappropriate use of affixes (16), omission of affixes (12), sounds that should be luluh are not dilulukan (10), incorrect determination of basic forms (7), incorrect repetition of compound words (4). These errors reflect the lack of attention of news writers to the rules of Indonesian morphology.